Respect of a Career and Europe - Szűcs, Petra (Public Finance Quarterly, 2025)
Review of the book entitled “Domi esse et in Europe et in mundo – Ünnepi tanulmányok a 70 éves Halmai Péter  tiszteletére” by Gábor Kutasi (ed.)